2017
DOI: 10.1002/2017gl075798
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism for Upper Crustal Fluid Flow Driven by Solitary Porosity Waves in Rigid Reactive Media?

Abstract: The equations governing the interaction of viscous deformation with porous flow of fluids give rise to wave‐like solutions. Such solutions have been explored in the context of melt and fluid flow in the mantle and crust at high temperatures, where ductile behavior occurs. Now it has been shown that the coupling of the kinetics of chemical reactions with fluid flow may give rise to similar solutions. This opens intriguing new possibilities. Porosity waves may arise in low‐temperature regimes, and may become mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Another issue is a scaling problem: porosity waves are expected to occur and evolve at scales (meters to kilometers) that do not lend themselves easily to high‐pressure and elevated temperature laboratory experimentation (scales of millimeters to centimeters) under conditions at which the rock and its constituents deform in a viscous or plastic manner. The latter is a prerequisite for modeling (Chakraborty, ). Our preliminary results (Räss et al, ) and the data presented here show that high‐permeabile pathways are most likely to form in low‐permeable clay‐rich materials and that these pathways can be observed at laboratory timescales (weeks to months).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is a scaling problem: porosity waves are expected to occur and evolve at scales (meters to kilometers) that do not lend themselves easily to high‐pressure and elevated temperature laboratory experimentation (scales of millimeters to centimeters) under conditions at which the rock and its constituents deform in a viscous or plastic manner. The latter is a prerequisite for modeling (Chakraborty, ). Our preliminary results (Räss et al, ) and the data presented here show that high‐permeabile pathways are most likely to form in low‐permeable clay‐rich materials and that these pathways can be observed at laboratory timescales (weeks to months).…”
Section: Discussionmentioning
confidence: 99%
“…The application of decompaction weakening (e.g., Connolly & Podladchikov, 1998 and the consideration of viscous shear deformation of the solid (Räss et al, 2019) enables a significant channelization of porosity waves for two-and three-dimensional (2D and 3D) flow. Furthermore, Omlin et al (2017) show that the coupling of the kinetics of chemical reactions with fluid flow may enable porosity waves also to potentially arise in low-temperature regimes, so that the porosity waves are not necessarily limited to the high-temperature viscous regions (Chakraborty, 2017). Moreover, Jordan et al (2018) show that mass, and hence melt, can be transported in 2D and 3D porosity waves; a fact that has been doubted based on 1D porosity wave studies.…”
Section: 1029/2021gc009963mentioning
confidence: 99%
“…A key question pertaining to the fluid-assisted formation of the Maiolica breccia is the origin of the hydrothermal fluids for hydraulic fracturing. Recent studies showed that expulsion of fluids from the plastic zone by sudden increases in porosity and permeability can form channelized fluid flows at velocities much greater than the background flow rate determined by Darcy's Law (Connolly and Podladchikov, 2015;Chakraborty, 2017;Jordan et al, 2018). The rapid fluid flow is also found to be associated with high fluid pressure close to lithostatic pressure.…”
Section: Model Of Maiolica Breccia Formationmentioning
confidence: 99%